Penerapan Terapi Jalan Kaki 20 Menit terhadap Penurunan Tekanan Darah pada Lansia dengan Hipertensi di Sukomangu Kabupaten Wonogiri - Wibowo Alqki Alianza; Mulyaningsih Mulyaningsih (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Background: The prevalence of elderly hypertension in the world according to WHO data is approximately 972 million people or 26.4% of people worldwide have hypertension, which is likely to continue to increase.The prevalence of elderly people in Indonesia in 2020 reached 10.7% of the total population.The prevalence of hypertension in Central Java Province based on the criteria for measuring hypertension in the population in 2019 reached 37.2%, in 2020 it reached 32.9% and in 2021 it reached 50.9% of the decline in all organ functions in blood vessels. Objectives: To describe the results of the application of 20-minute walking therapy in elderly patients with hypertension in the Sukomangu Village area, Purwantoro District. Method: Case study is a series of scientific activities carried out intensively, at the beginning of the study, interviews and blood pressure measurements were carried out on the respondents, then after the application, blood pressure measurements were carried out again on the respondents. Results: There was a decrease in blood pressure after giving 20-minute walking therapy to Mrs. W. and Mrs. K from stage 2 hypertension to stage 1 hypertension.Conclusion: The application of 20-minute walking therapy can potentially reduce blood pressure in the elderly with hypertension in both respondents.